Evolução das pesquisas acadêmicas sobre auditoria no Brasil no período 1999 a 2018 - Barthold, Shirley (2020)
The topics of audit research in the national literature were categorized in order to classify the themes of audit research in Brazilian scientific publications on the subject from 1999 to 2018 and, at the same time, to verify whether the adoption of IFRS impacted production audit. Specifically, the authors, the most relevant journals and the keywords most used in auditing were identified, and the recurring themes were estimated by applying the three laws of Bibliometry (Lotka's Law for authors' productivity, Bradford's Law for productivity and Zipf Law to map the most used keywords). The study sample consisted of 282 articles from 31 journals found on the Sucupira CAPES Platform, for the period 1999 and 2018. The themes Audit Market (MRKT), Continuity Opinions (GCOP), Profession (PROF), Audit Research (RESE), International Regulation (INTR), Audit Report and Financial Statement Users (REPO), Audit Committee (ACOM), Corporate Governance (CGOV), External Audit (EXTE) and Education (EDUC) were the most relevant topics in sample items. It was also identified that the topics Relationship on Audit (RELA), Environmental Audit (AMA), Operational Audit (OPA) and Ethics and / or Moral (ETHI) are four new themes that have been cataloged. It was possible to observe a marked growth in the volume of articles published in the main journals considered in this work from 2009 to 2018. This period coincided with the adoption of IFRS, as well as with the increase in accounting graduate programs in Brazil. The research results provide evidence that the expansion of postgraduate accounting courses in recent years in Brazil, as well as the adoption of IFRS, may have intensified the production of academic articles in accounting and, consequently, auditing.